2002
DOI: 10.1161/01.cir.0000016722.37138.f2
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Regeneration Therapy for Heart Failure

Abstract: Background — We hypothesized that transfection of the gene for human hepatocyte growth factor (hHGF) combined with cellular cardiomyoplasty might regenerate the impaired myocardium. Methods and Results — We used a ligation model of proximal left anterior descending coronary artery (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
44
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(46 citation statements)
references
References 32 publications
1
44
1
Order By: Relevance
“…Typically, transgene expression levels after adenovirus-mediated transfer are transient, lasting only 4--6 weeks. 27,28 This raises the possibility that the functional recovery in the study of Miyagawa et al 26 and our study became less prominent late after gene transfer, whereas that in other positive studies was prominent early after gene transfer, probably because the antiapoptotic and antifibrotic effects of HGF gene therapy on ventricular remodeling and dysfunction may be transient and be lost after HGF expression ceases.…”
Section: Discussioncontrasting
confidence: 45%
See 3 more Smart Citations
“…Typically, transgene expression levels after adenovirus-mediated transfer are transient, lasting only 4--6 weeks. 27,28 This raises the possibility that the functional recovery in the study of Miyagawa et al 26 and our study became less prominent late after gene transfer, whereas that in other positive studies was prominent early after gene transfer, probably because the antiapoptotic and antifibrotic effects of HGF gene therapy on ventricular remodeling and dysfunction may be transient and be lost after HGF expression ceases.…”
Section: Discussioncontrasting
confidence: 45%
“…In the previous studies, 5--8,10--13,15--17 the positive functional recovery was observed at 2--6 weeks after HGF gene transfer, whereas we repeated the measurement of LV function at a relatively long-term time point of 10 weeks after the gene transfer. Although we could not perform cine MRI at three different time points because of its limited availability, Miyagawa et al 26 measured LVEF and percentage fractional shortening by echocardiography 3 times up to 8 weeks and, interestingly, reported slight improvement in the functional parameters at 4 weeks and their return to baseline levels at 8 weeks in the HGFtreated group. Typically, transgene expression levels after adenovirus-mediated transfer are transient, lasting only 4--6 weeks.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Moreover, in clinical settings, preinfarction treatments are not practical. Recently, Miyagawa et al 12 injected hemagglutinating virus of Japan (HVJ)-liposomes bearing the human HGF gene directly into the postinfarction rat heart but found no beneficial effects on ventricular remodeling or dysfunction. They started the therapy 2 weeks after MI, which we assume may have been too late to be effective.…”
mentioning
confidence: 99%